Postinfectious Autoimmune Syndrome as a Key Factor in Chronization of the Infectious Disease - Cherepahina, Natalia; Agirov, Murat; Tabaksoeva, Jamilyia; Ahmedilova, Kusum; Suchkov, Sergey (IntechOpen, 2011)
None